2022
DOI: 10.1002/fsn3.2987
|View full text |Cite
|
Sign up to set email alerts
|

Morphological diversity, phenolic acids, and antioxidant properties in eryngo (Eryngium caucasicum Trautv): Selection of superior populations for agri‐food industry

Abstract: Eryngo (Eryngium caucasicum Trautv) a widespread species of the Apiaceae reveals high nutritional value and therapeutic properties due to the significant content of biologically active metabolites such as essential oils, phenolic compounds, and flavonoids. The present study was performed to evaluate the morphological and biochemical variability and antioxidant properties of naturally grown populations of eryngo.One-way ANOVA showed significant (p < .01) differences in the majority of parameters measured among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The variation in the concentration of rosmarinic acid due to the Po × C interaction ranged from 5011.3 to 9674.8 µg g −1 . Hatami et al [ 33 ] also identified a large amount of variation in the contents of rosmarinic acid in Eryngium caucasicum Trautv in six geographic regions of Iran (ranging from 0.118 to 1.234 µg g −1 ) by means of HPLC, and their results showed high levels of variation within each geographic location of origin, with a coefficient of variation equal to 50.81%. In contrast, Kikowska et al [ 34 ] estimated 495 and 4309 µg g −1 concentrations of rosmarinic acid in the roots of E. maritimun L. grown in the field and in seedlings grown in vitro, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The variation in the concentration of rosmarinic acid due to the Po × C interaction ranged from 5011.3 to 9674.8 µg g −1 . Hatami et al [ 33 ] also identified a large amount of variation in the contents of rosmarinic acid in Eryngium caucasicum Trautv in six geographic regions of Iran (ranging from 0.118 to 1.234 µg g −1 ) by means of HPLC, and their results showed high levels of variation within each geographic location of origin, with a coefficient of variation equal to 50.81%. In contrast, Kikowska et al [ 34 ] estimated 495 and 4309 µg g −1 concentrations of rosmarinic acid in the roots of E. maritimun L. grown in the field and in seedlings grown in vitro, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It is the largest and possibly the most taxonomically complex genus of the Apiaceae family [ 2 ]. Preparations of different Eryngium species are used in folk medicine, as they have the following therapeutic actions: antioxidant [ 7 , 8 , 9 , 10 ], anti-inflammatory [ 11 ], cytotoxic [ 10 , 12 , 13 , 14 , 15 ], antibacterial [ 16 , 17 , 18 , 19 , 20 , 21 ], antifungal [ 19 ], diuretic [ 11 ], antiallergic [ 11 ], etc. Today, the need to develop the technology of medicines from raw materials of unexplored endemic medicinal plant species of Kazakhstan is an urgent task of domestic pharmacy [ 22 ].…”
Section: Introductionmentioning
confidence: 99%